HOMOSEKSÜEL VE HETEROSEKSÜEL BİREYLERDE YAŞANTISAL KAÇINMA, DEĞER ODAKLILIK VE DEPRESYON-ANKSİYETE-STRES ARASINDAKİ İLİŞKİLERİN İNCELENMESİ - Çakmak, Zeynep; Aktürk, İlker; Yaman, Ömer Miraç (Fırat University, 2023)
Bu araştırma, kendini homoseksüel veya heteroseksüel olarak tanımlayan bireylerde yaşantısal kaçınma, değer odaklı yaşam ve depresyon-anksiyete-stres arasındaki ilişkiyi belirleme ve homoseksüel bireylerde değer odaklılığın depresyon, anksiyete ve stres puanlarını yordama gücünü tespit etmek amacıyla gerçekleştirilmiştir. Araştırma grubu 184’ü homoseksüel, 175’i heteroseksüel olmak üzere 359 kişiden oluşmaktadır. Verilerin analizi için Bağımsız Gruplar t-Testi, Pearson çarpım moment korelasyon analizi, Çoklu Standart Regresyon analizi yapılmıştır. Araştırmanın bulguları; eşcinsel davranış eğilimi gösteren bireylerde değer verme ölçeği ilerleme ve tıkanma alt boyutlarının depresyonu %46 (r = .679; p

This study was conducted to determine the relationship between experiential avoidance, value-oriented life, and depression-anxiety-stress in individuals who identify themselves as homosexual or heterosexual and to reveal the predictive power of value orientation on depression, anxiety, and stress scores in homosexual individuals. A total of 359 people were included in the study, 184 of whom are homosexuals and 175 are heterosexuals. The data were analyzed using Independent Group's t-Test, Pearson product-moment correlation analysis, and Multiple Standard Regression analysis. The results of the study show that the progression and obstruction sub-dimensions of the VQ significantly predict depression by 46% (r = .679; p
Examination of the Relationships between Experiential Avoidance, Value Orientation and Depression-Anxiety-Stress in Homosexual and Heterosexual Individuals
Keywords: Gender; Sexuality and Education; Cinsiyet; Cinsellik ve Eğitim